2013 38th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) 2013
DOI: 10.1109/irmmw-thz.2013.6665732
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz transceiver microprobe for chip-inspection applications using optoelectronic time-domain reflectometry

Abstract: In this work a compact microprobe for advanced chip-inspection applications is introduced. The probe features integrated photoconductive switches for Terahertz pulse generation and detection. Device application is demonstrated for contact-free high-resolution time-domain reflectometry measurements at silicon-chip test structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Nagel et al demonstrated successful microprobe analysis of a device under test DUT structure: a typical Cu-based coplanar waveguide with an electrode width of 50 μm, 30 μm spacing, and 3 μm copper thickness based on an undoped Si substrate. 144 A 75-nm-thick layer of SiO 2 is deposited between the electrodes and substrate. This method is very effective for determination of open-end, full short-cut, and semi-short-cut defect via analysis of the peak or trough of the TDR signal after probe coupling.…”
Section: Time-domain Reflectancementioning
confidence: 99%
“…Nagel et al demonstrated successful microprobe analysis of a device under test DUT structure: a typical Cu-based coplanar waveguide with an electrode width of 50 μm, 30 μm spacing, and 3 μm copper thickness based on an undoped Si substrate. 144 A 75-nm-thick layer of SiO 2 is deposited between the electrodes and substrate. This method is very effective for determination of open-end, full short-cut, and semi-short-cut defect via analysis of the peak or trough of the TDR signal after probe coupling.…”
Section: Time-domain Reflectancementioning
confidence: 99%